Central African Republic : Poverty Reduction Strategy Paper; First Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses key findings of the first annual progress report on the Poverty Reduction Strategy Paper (PRSP) for Central African Republic. The first year of PRSP implementation was characterized by an unfavorable international economic environment, with its repercussions on the national economy. The various external shocks have led to instability in budget resources, a surge in inflation, an aggravated foreign trade deficit, and slowed growth. Despite this unfavorable economic cycle, with the help of its development partners, the government has established an institutional framework for PRSP implementation, monitoring, and assessment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet